(3GdYedjGJ GdeUQajI GdESdGejI (B:s (3GdWQb GdeMGSHjI GdMOjKI (B/s - (3YHO Gddg, NGdO Cejfs; (3SYjaGf, MSjf SYjO s ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2011)
(3eONd Gdi GdYed GdeUQaj(B- (3GdUjQaI GdESdGejI(B- (3GdfXGe GdeMGSHj aj GdHfhc(B- (3eMGSHI bSe GdNRjfI(B- (3eMGSHI bSe GdhOGFY(B- (3eMGSHI bSe GdceHjGdGJ(B- (3eMGSHI GdeQGHMI hGdeQGHMI ddBeQ HGdTQGA(B- (3eMGSHI GdJehjd HGdeVGQHI(B- (3eMGSHI GdJehjd HGdeTGQcI(B- (3eMGSHI GdSde hGdSde GdehGRj(B- (3eMGSHI GdELGQI hGdELGQI GdefJgjI HGdJedc(B- (3eMGSHI GdESJUfGY hGdESJUfGY GdehGRj(B- (3eMGSHI GdHjY GdBLd(B- (3eMGSHI GdESJKeGQGJ(B- (3eMGSHI GdcaGdGJ GdeUQajI(B- (3eMGSHI GdEYJeGOGJ GdeSJfOjI(B- (3eMGSHI HhGdU GdJMUjd(B- (3eMGSHI GdMhGdGJ(B- (3eMGSHI JCLjQ GdUfGOjb GdMOjOjI(B- (3eMGSHI HWGbI GdEFJeGf(B- (3EYOGO GdMSGHGJ GdNJGejI hGdbhGFe GdeGdjI aj GdHfhc(B- (3GdcThaGJ hGdJbGQjQs
(3GdeQGLY U(B.659s
Keywords: (3GdeMGSHI, GdEbJUGO GdESdGejs; (3GdeUGQa GdESdGejIs